Sayer Variety, Seed Oil and Introduction of Fatty Acids into Certain Types of Therapeutic and Food Ration of The Fatty Acid Extraction from Iraqi Date Palm (Phoenix Dactylifera L.) - et al., Nwaedh Mahdi Hanoon Nwaedh (International Journal of Advanced Science and Technology, 2020)
This study was carried out in order to extract oil from date palm (Phoenix dactylifera L.). sayer variety, using Soxhlet extraction method. The content of the oil extracted from saturated and unsaturated fatty acids was examined and diagnostic tests were run with GC/MS (Gas Chromatography / Mass Spectrometry).